A prática clínica no cenário da sala com espelho unidirecional: percepção dos alunos sobre o método de observação direta no ensino médico - Marchi, Elizabete Garcia Ferreira Arroyo (2018)
Introduction: For the medical training recommended in the Curriculum Guidelines, changes in the teaching-learning process are necessary, making the student an active element in knowledge construction, using new scenarios as assistance tool. Objective: To evaluate the applicability and acceptance of Direct Observation Method in a room with a one-way mirror, as a learning practice in competences development of 6th period Medical graduation course students. Methods: It is an exploratory, analytical and qualitative research. After approval by the Research Ethics Committee, three focus groups were carried out, totaling 30 students who attended, from February to June 2016, the referred scenario where an academic performs real patient’s care with establishment of the patient-medical relationship, anamnesis, clinical examination and diagnostic reasoning, while the tutor and the other 11 students looked through the mirror. After the clinical examination, the tutor and the evaluated student take the necessary steps for the case. After the patient leaves, the examiner student performed a self-assessment and a feedback is given by the other students and tutor. The data obtained in the focus groups were analyzed using the methodological approach of content analysis, thematic modality of Bardin. From these results emerged the final product in the form of a conceptual map, based on the Grounded Theory. Results: The recorded units were identified from collected data, distributed in subcategories and condensed into three categories (reflexive learning, formative evaluation and transforming scenario). The teaching strategy was highly accepted by the students. As fragile points indicated were the impossibility of following patients after the consultation, some technical problems (such as the sound system), the fact that not all of them had passed through the examiner's experience (a fact that has already been corrected after the focus groups) and, as a strong point, collective, reflexive and experiential learning, believing that it could be extended to other curricular units. Conclusion: The unusual scenario, although real, the awareness of being observed and evaluated had a positive influence on learning. The one-way mirror room has applicability and it has been well accepted as a practice scenario by the research participants resulting in meaningful learning experience